The Effect of Numbered Head Together and Question Answer Relationship Techniques on Students Reading Comprehension : A Comparative Study - ., NURUDDIN; ., Prof. Dr.I Ketut Seken,MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris, 2013)
The objectives of the study was, first, to investigate whether there is a significant effect of numbered head together and question answer relationship technique on studentsÃ¢â¬â¢ reading comprehension; second to compare the effect of NHT and that of QAR on reading comprehension. Conducted at the eighth grade students of MTs Birrul Walidain NW Rensing in the school year of 2012-2013, this study used posttest only control group design. The sample used was obtained by cluster random sampling technique. The total number of sample was 66 students, divided into three groups; NHT,QAR and conventional technique groups. The study involved 6 sessions of treatment and at the end of the treatments, a reading comprehension posttest was conducted . The data were analyzed by using descriptive statistics and inferential statistics, namely One way Anova and T-Scheffe. The study found that first, there is a significant difference in reading comprehension among students who are treated using NHT,QAR and those treated using the conventional reading technique. Second, there is a significant difference in reading comprehension between students who are treated using NHT technique and those treated using the conventional reading technique. Third, there is a significant difference in reading comprehension between students who are treated using QAR technique and those treated using the conventional reading technique. Fourth, there is no significant difference in reading comprehension between students who are treated using NHT and those treated using QAR technique. In conclusion NHT is likely higher in effectiveness than the other techniques in improving the reading comprehension. keyword : Numbered Head Together, Question Answer Relationship Techniques, Conventional Reading Technique and reading comprehension